Factors affecting Total Quality Management Implementation on Service Industry: A Systematic Literature Review - Chandra Hosen; Ardhianiswari Diah Ekawati; Anita Maharani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Companies in the service industry are trying to make changes to meet the needs of the company and the needs of customers. Over the last few years, Total Quality Management has been developed and is one way to provide various changes in improving the quality of relationships with consumers. The purpose of this research is to find out what factors influence the implementation of Total Quality Management in the service industry using a systematic literature review (SLR). Search databases and article sources using the Harzing's Publish or Perish application. Database sources vary from Science Direct, Emerald, Springer, SSRN Papers, Growing Science, Cogentoa, Research Gate and Academia. Meanwhile, the keyword to search the database is Total Quality Management and Service Industry. After the SLR process was carried out to the previous studies that fulfill criteria of the keywords, there were 5 factors that were mentioned the most in almost all studies: top management commitment, continuous improvement, focus on customers, training and education as well as employee management and involvement.